2022
DOI: 10.1080/02699931.2022.2105819
|View full text |Cite
|
Sign up to set email alerts
|

Mothers need more information to recognise associated emotions in child facial expressions

Abstract: Infant and child faces receive more attention than adult faces, especially when they are portraying emotions. This preferential treatment is increased in mothers. It is unclear how this affects the ability to recognise child emotions and at which age children lose this preferential treatment. Using morphed videos where a neutral face continually and gradually takes on an emotion, we were able to quantify the amount of information needed to identify the emotion. We investigated amount of information needed as w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…We used the correction following Westfall's method 72,73 using a Matlab code (written for statistical tests with one comparison (e.g., Mann-Whitney-U, T-test or post-hoc test after an ANOVA) published on OSF (https:// osf. io/ twxsk/ 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used the correction following Westfall's method 72,73 using a Matlab code (written for statistical tests with one comparison (e.g., Mann-Whitney-U, T-test or post-hoc test after an ANOVA) published on OSF (https:// osf. io/ twxsk/ 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…The differences observed between the two age groups in other domains could be attributed to parents' greater difficulty in recognizing emotions in preschool children compared to older ones. Previous studies have indicated that mothers of preschool-aged children require more information to accurately identify emotions in children's facial expressions (23). Additionally, some questionnaire items related to functions and participation might not be expected by parents of younger children to be achievable.…”
Section: Discussionmentioning
confidence: 99%